Muigaia, a new Paleotropical genus of Convolvulaceae - Simon Wachira Ngima; Vivian Kathambi; Samuel Paul Kagame; Sushant More; Lauren A. Eserman; Rafael Felipe de Almeida; Benoit Loeuille; Marc S. M. Sosef; Patrick Chalo Mutiso; Higor Antonio-Domingues; Lars W. Chatrou; Ana Rita Simões (Kew Bulletin, 2026)
Summary A new genus of Convolvulaceae, Muigaia , is here proposed and fully revised, including molecular phylogenetic analyses, comprehensive morphological and palynological descriptions, identification keys, distribution maps and conservation assessments. It is a strictly paleotropical genus, occurring in Tropical Africa, Madagascar, India and Australia, and remarkably absent from the Malesian region. It is distinctive for the markedly angular stems; deeply palmately lobed, irregularly dissected leaves; leaf-like stipules at the base of the petiole; muricate, verrucose or cristate sepals; a 3-globose stigma and a 6-valved capsule. A revision of the species involved in this complex has resulted in the recognition of a total of seven species, including five new combinations, one new name ( M. shimpalei ) and one newly described species ( M. australiana ), endemic to Australia. The tropical African specimens of M. coptica , in particular, exhibit a wide range of morphological variation and should be investigated in detail. We expect that, now that Muigaia has been phylogenetically and morphologically circumscribed, further revisionary studies could focus on improving the species delimitation, and likely result in the discovery of additional new species to science.